The Circular RNA CircCOL1A1 Functions as a miR-149-5p Sponge to Regulate the Formation of Superior-Quality Brush Hair via the CMTM3/AR Axis - Wang, Jian; Wu, Xi; Sun, Xiaomei; Zhang, Liuming; Wang, Qiang; Qu, Jingwen; Wang, Yanhu; Li, Yongjun (Frontiers in Cell and Developmental Biology, 2022)
Superior-quality brush hair, also called Type III hair, can be obtained only from the cervical spine region of skin tissues of Yangtze River Delta white goats. The formation of superior-quality brush hair is controlled by a series of critical genes and related signaling pathways. Circular RNAs (circRNAs) are ubiquitous endogenous noncoding RNAs that regulate many biological and physiological processes in mammals. However, little is known about the potential regulatory role of circRNAs in superior-quality brush hair formation. Here, we analyzed circRNA sequencing data from cervical spine region skin tissues of normal-quality brush hair goats and superior-quality brush hair goats and then selected and identified the differentially expressed circRNA circCOL1A1. To investigate the regulatory role and mechanism of action of circCOL1A1, goat hair follicle stem cells (gHFSCs) were cultured and treated with a circCOL1A1 overexpression plasmid and small-interfering RNAs (siRNAs). Functional assays showed that circCOL1A1 knockdown promoted the proliferation and differentiation of gHFSCs cultured in vitro but inhibited stem cell apoptosis, whereas overexpression of circCOL1A1 suppressed stem cell proliferation and differentiation and induced apoptosis. Bioinformatics analysis combined with dual-luciferase reporter assays and RNA binding protein immunoprecipitation (RIP) verified that, mechanistically, circCOL1A1 could bind miR-149-5p directly and then relieve its inhibitory effect on CMTM3 to further control the CMTM3/AR axis. Collectively, our results reveal a novel regulatory pathway for the formation of superior-quality brush hair and indicate that circCOL1A1 plays a role in gHFSC growth and superior-quality brush hair formation by targeting the miR-149-5p/CMTM3/AR axis.